Evaluation the diuretic activity of the aqueous extract of Ephedra alata and Plumbago europaea in Mice - Amnah Raba; Maram Hroub; Sujud Khwailed (My University, 2016)
Background: Throughout history, man used various natural materials as a remedy for treatment of various diseases and recently witnessing a vastly growing and renewed interest in herbal medicine globally. In Palestinian folk medicine E. alata and P. europaea used as diuretics and for treatment of hypertension. This study aimed to evaluate the diuretic and acute toxicity effects of the aqueous extracts for these two plants in mice after oral administration. Methods: Adult mice were administered orally aqueous E. alata and P. europaea extracts (500 mg/kg). Urine output and electrolyte contents were then quantified up to 4 h and compared with those administered with furosemide 10 mg/kg as a positive control group and normal saline as a negative control group. Results: The aqueous extract of E. alata produced significant diuresis (p < 0.001), while the P. europaea aqueous extract had shown mild dieresis, but statistically not significant by the end of the forth hour compared to control mice. Moreover, both aqueous extracts had an alkaline pH and a mild increase in the electrolyte excretion (Na, K). Conclusion: Our investigations strongly revealed that E. alata aqueous extract had potential diuretic effect which can be utilized for treatment of hypertension and other diseases related to the dieresis also for manufacturing natural and safe diuretic drug.